Heterocyclic Polymethine Dyes : synthesis, properties and applications - Strekowski, Lucjan (Springer, 2017)
Synthesis of Cyanine Dyes -- Cyanine Dye–Nucleic Acid Interactions -- Near-Infrared Cyanine Dye–Protein Interactions...